Refugee entrepreneurship: Systematic literature review - Jan Brzozowski; Inna Voznyuk (International Entrepreneurship Review)
Objective: The objective of this article is to systematically analyse the current academic research on refugee entrepreneurship in Europe and beyond. Refugee entrepreneurship represents a burgeoning area of study that has become increasingly significant following the European migrant crisis in 2015 and the full-scale Russian invasion of Ukraine in 2022. We seek to determine how studies on refugee entrepreneurship differ in their theoretical approaches and methodologies from traditional research on immigrant and ethnic entrepreneurship.